Gambaran Karies dan Evaluasi Perawatan pada Siswa di Kawasan Puskesmas Ikur Koto, Padang, Sumatera Barat: Caries Description and Treatment Evaluation on Students in Public Health Center of Ikur Koto Health, Padang, West Sumatra - Regia Aristiyanto; Wulan Anggestia; Hasan Barquelian; Nia Wijayanti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Caries are still a significant problem in oral and dental health worldwide, including Indonesia. Various efforts must continue to be made to reduce the incidence of caries, both promotive and preventive, as well as curative and rehabilitative. Based on the Riset Kesehatan Dasar 2018, 36.71% of the people of Padang City have cavities/injured/toothache. Of the youth aged 15-24, 37.45% had cavities/injured/toothache. This program aims to get an overview of caries classification and provide appropriate treatment. The overview of caries classification can become data on the pattern of caries development so that strategies for dealing with earlier caries can be carried out appropriately, effectively, and efficiently. The implementation of the present program was carried out through a thorough and comprehensive examination of the oral cavity; then, treatment was carried out according to the complaints and cases found. The post-treatment evaluation was carried out by distributing questionnaires to participants afterward. Based on the depth of caries treated, 57.14% were dentin caries. Caries classification based on G.V. Black showed that Class I cavity was the highest incidence (64.29%). Mount and Hume's classification presented class 1.3 (39.28%) as the highest, while based on the ICDAS classification, it was class D3 (46.44%). The post-treatment evaluation showed that all participants (100%) stated that the condition of the teeth improved and that there were no complaints/discomfort after treatment.